AN ANALYSIS ON CODE MIXING USED BY YOUTH IN KINIAR - Yulita R. Mawuntu; Deane Wowor; Tirza Kumayas (Journal of English Culture, Language, Literature and Education, 2020)
This research was conducted to identify the forms of code mixing and to describe the social contexts where the youth it was conducted in Kiniar, one of the villages in Tondano used code mixing in their daily communication. Qualitative research design was used in this research. The data were collected in the form of words and phrases, not numbers. The data was taken based on participant observation. and the data were collected by taking note. This research used the theory of Siregar. The data were collected and analysed used the theory of Bogdan and Biklen. The results of this research showed that there are 4 codes used by youth in GMIM Tiberias Kiniar Church: Indonesia language, English language. Manado-Malay language and Toulour language. But Manado-Malay is dominantly used. The data were categorized into types of code mixing: Intra sentential mixing and Extra-sentential mixing. In relation to the result of the study, the researcher suggested that code mixing is not a barrier in communicating or saying something to people, but it may be considered as a useful strategy in communicating to people in formal or non-formal forum, cases, or situation, if the aim is to make clearer the meaning or the message of the speaker to the people or the audiences.